Проекти архівної реформи: основні положення та спроби втілення - Матяш, І. (Архіви України, 2008)
The article analyses the archival reform projects developed in Russia and Ukraine. It contains a review of major principles of the archival affairs reform defined by D. Samokvasov, H. Rozenkampf, M. Kalachov, O. Hrushevskyi, V. Modzalevskyi. The archival reform projects have proved to be the main theoretical outcomes of the first archival authorities in Ukraine.